(untitled) (Research, Society and Development, 2022)
COVID-19 (Novel Coronavirus) is a viral infectious disease transmitted by the SARS-CoV-2 agent, which in March 2020 reached the status of a global pandemic. Despite being related to a series of systemic disorders, especially respiratory and renal, the development of vaccines allowed COVID-19 to have a decrease in its number of cases, especially serious conditions and deaths. Therefore, the objective of this study was to analyze the relationship between confirmed cases of COVID-19 and variables related to sex, race and age, in individuals affected in the city of Salvador-BA. For this, a search was carried out for updated data referring to the indicators of such a disease in the described municipality, at the electronic address of the Municipal Secretary. Among the results presented, from the total of 267,936 confirmed notifications, there was a higher prevalence in female individuals (55%), of mixed race (39%), aged between 30-39 years, and 40-49 years, both with (23%). Through this study, a presentation can be made to the scientific community about the epidemiological profile of those affected by COVID-19 in the city of Salvador, Bahia. In this way, the results presented by this study can be taken into account by public agencies, when making decisions regarding municipal public health.